Kepentingan Nasional Amerika Serikat Dalam Penerapan Pajak Produk Baja Dan Aluminium China Tahun 2018 - Fragrans, Eling Puspa Myristica; Hartati, Anna Yulia (Kajian Hubungan Internasional, 2023)
The United States National Interest in the Implementation of China's 2018 Steel and Aluminum Product Tax aims to find out the reason Donald Trump imposed China's steel and aluminum tax in 2018. The research used by the author uses qualitative research based on literature reviews such as from books, journals and other mass media. The author uses the theory of national interest. Where, this theory is used to determine the goals and interests of the United States. The results of this theory found two reasons why the United States imposed a tax on China's steel and aluminum products in 2018. Political interests and economic interests are the reasons Donald Trump imposed a tax on China's steel and aluminum products in 2018. The trade war between the United States and China has raises pros and cons in various parts of the world. The trade war launched by Donald Trump as president of the United States certainly has national goals and interests for his country. The taxes imposed by Donald Trump on aluminum and steel against China led to reciprocal action from China to the United States as well. But China is not standing still. China reported Trump's actions to the World Trade Organization (WTO). The United States has also been sanctioned for this action.